Information Production and Capital Allocation: Decentralized versus Hierarchical Firms - Stein, Jeremy C. (Journal of Finance, 2002)
ABSTRACT This paper asks how well different organizational structures perform in terms of generating information about investment projects and allocating capital to these projects. A decentralized approach‐with small, single‐manager firms‐is most likely to be attractive when information about projects is “soft” and cannot be credibly transmitted. In contrast, large hierarchies perform better when information can be costlessly “hardened” and passed along inside the firm. The model can be used to think about the consequences of consolidation in the banking industry, particularly the documented tendency for mergers to lead to declines in small‐business lending.